Revisiting Person Re-Identification by Camera Selection - Peng, Yi-Xing (IEEE transactions on pattern analysis and machine intelligence, 2024)
Person re-identification (Re-ID) is a fundamental task in visual surveillance. Given a query image of the target person, conventional Re-ID focuses on the pairwise similarities between the candidate images and the query. However, conventional Re-ID does not evaluate the consistency of the retrieval results of whether the most similar images ranked in each place contain the same person, which is risky in some applications such as missing out a place where the patient passed will hinder the epidemiological investigation. In this work, we investigate a more challenging task: consistently and successfully retrieving the target person in all camera views. We define the task as continuous person Re-ID and propose a corresponding evaluation metric termed overall Rank-K accuracy. Different from the conventional Re-ID, any incorrect retrieval under an individual camera view that raises an inconsistency will fail the continuous Re-ID. Consequently, the defective cameras, in which the images are hard to be automatically associated with the images from other views, strongly degrade the performance of continuous person Re-ID. Since the camera deployment is crucial for continuous tracking across camera views, we rethink person Re-ID from the perspective of camera deployment and assess the quality of a camera network by performing continuous Re-ID. Moreover, we propose to automatically detect the defective cameras that greatly hamper the continuous Re-ID. Because brute-force search is costly when the camera network becomes complicated, we explicitly model the visual relations as well as the spatial relations among cameras and develop a relational deep Q-network to select the properly deployed cameras and the un-selected cameras are regarded as the defective cameras. Since most existing datasets do not provide topology information about the camera network, they are unsuitable for investigating the importance of spatial relations on camera selection. Thus, we collect a new dataset including 20 cameras with topology information. Compared with randomly removing cameras, the experimental results show that our method can effectively detect the defective cameras so that people could take further operations on these cameras in practice (https://www.isee-ai.cn/∼yixing/MCCPD.html)